1978
DOI: 10.1111/j.1365-2230.1978.tb01495.x
|View full text |Cite
|
Sign up to set email alerts
|

The long-term treatment of acne vulgaris

Abstract: Summary A clinical investigation of 57 patients with moderate acne indicated that the response to treatment with long‐term antibiotics and appropriate topical therapy could be divided into three groups. One group of patients (28%) showed an 80% improvement within 4 months of starting treatment. In 37% such an improvement took 12 months and in a third group (35%) only a 57% improvement was obtained at the end of 12 months. There was no obvious clinical reason for these three responsive groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…12,14,94,190 One clinical trial evaluating tazarotene 13 and one study involving maintenance with tretinoin after oral tetracycline and tretinoin topical treatment have been published. 191 Long-term use of adapalene has been studied, both with adapalene 0.3% and adapalene 0.1%/BPO 2.5%. 120,192 The recent maintenance therapy studies are summarized in Table VII. In the majority of these studies, topical retinoid monotherapy has been evaluated after an initial 12-week period of combination therapy involving a topical retinoid plus an oral or topical antibiotic.…”
Section: Consensus: Topical Retinoids Should Be First-line Agents In mentioning
confidence: 99%
See 1 more Smart Citation
“…12,14,94,190 One clinical trial evaluating tazarotene 13 and one study involving maintenance with tretinoin after oral tetracycline and tretinoin topical treatment have been published. 191 Long-term use of adapalene has been studied, both with adapalene 0.3% and adapalene 0.1%/BPO 2.5%. 120,192 The recent maintenance therapy studies are summarized in Table VII. In the majority of these studies, topical retinoid monotherapy has been evaluated after an initial 12-week period of combination therapy involving a topical retinoid plus an oral or topical antibiotic.…”
Section: Consensus: Topical Retinoids Should Be First-line Agents In mentioning
confidence: 99%
“…The studies have ranged from 3 to 12 months; however, the two longest studies (6 and 12 months, respectively) did not include a control arm. [12][13][14]94,190,191,193 Adapalene. There have been 4 controlled and two uncontrolled studies of adapalene gel 0.1% as maintenance therapy (Table VII).…”
Section: Consensus: Topical Retinoids Should Be First-line Agents In mentioning
confidence: 99%
“…Response to antimicrobial chemotherapy is sometimes slow and fails to alleviate the symptoms in some patients (Leyden, 1976;Gould and Cunliffe, 1978). A number of unrelated factors that might contribute to failure of therapy have been considered, including antibiotic resistance in propionibacteria (Leyden, 1976;Cunliffe et al, 198 1) but because resistance was not commonly observed it seemed unlikely to be an important cause of treatment failure (Leyden, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…There are over 1000 reports of effective treatment for acne; unfortunately many papers are of little scientific value because of the lack of adequate objective assessment of acne and placebo groups. AH except two (Cornbleet, 1961;Gould & Cunliffe, 1978) relate to the treatment of acne for 2 or 3 months with no follow-up. Clinical experience dictates that acne often requires treatment for many months or even years and highlights an important gap in the published literature regarding the long-term management of acne.…”
Section: Review Of Existing Treatment For Acnementioning
confidence: 99%